Study of Traumatic Ankle Injuries in Taif, Saudi Arabia, Using Magnetic Resonance Imaging - Kajoak, Samih (International Journal of Innovative Research in Medical Science, 2022)
Background: Ankle injuries occur frequently and represent around 10% of all emergency department admissions. The preferred diagnostic modality for evaluating ankle injuries is Magnetic resonance imaging, because of its better soft tissue contrast; noninvasive imaging, as well as its scanning capability in several planes. Aims: This study aimed to highlight the importance of MRI in the assessment of patients with Ankle pain as a result of a traumatic injury in Taif, Saudi Arabia. Methods and materials: a retrospective study was carried out at King Abdulaziz Specialist Hospital in Taif, from October 2021 to February 2022. 56 traumatic patients were enrolled in the study. All images were evaluated by two expert radiologists. Results: Out of 56 patients; 31 (55%) were males and only 25 (45%) were females, the mean age was found to be 34. ± 12. Acute onset of pain was (82%) and (18%) was chronic. 44 (79%) of the respondents had joint effusion and 37 (66%) had ATFL Anterior Talofibular Ligament injuries. Regarding tendons injury, the most reported injury was tenosynovitis (14.3%). Deltoid ligament injury is significantly associated with age (P-value = .005), since those 35 years old or less are more frequently prone to have deltoid ligament injury (44%) than those more than 35 years old (9%). Conclusion: The MRI is the perfect modality of choice in the assessment of traumatic ankle injuries because it has higher sensitivity detection when compared to other modalities.